2020
DOI: 10.1016/j.rmcr.2020.101210
|View full text |Cite
|
Sign up to set email alerts
|

Intolerance to and limitations of inspiratory muscle training in patients with advanced chronic obstructive pulmonary disease: A report of two cases

Abstract: Inspiratory muscle training (IMT) has been attracting attention as one of the useful treatments in patients with chronic obstructive pulmonary disease (COPD). IMT is reportedly effective in most patients with COPD. However, little is known about the benefits of IMT, especially in patients with advanced COPD. We reported two cases of COPD that received 12-week IMT to explore intolerance to and the limitations of IMT in advanced COPD. The effectiveness of IMT was evaluated using cardiopulmonary exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…However, at least in patients with advanced COPD, no large studies have reported the adjunctive effects of inspiratory pressure load training added to PR [ 72 , 73 , 74 ]. In addition, Yamamoto et al reported that, especially in underweight patients with advanced COPD, inspiratory pressure load training might lead to tachypnea and wasted ventilation, which would in turn decrease exercise performance; however, this point was made as part of a case report [ 75 ]. Further studies are needed to evaluate the effect of expiratory or inspiratory pressure load training on exertional dyspnea in patients with COPD.…”
Section: Exercise Tolerance and Exercise-limiting Factorsmentioning
confidence: 99%
“…However, at least in patients with advanced COPD, no large studies have reported the adjunctive effects of inspiratory pressure load training added to PR [ 72 , 73 , 74 ]. In addition, Yamamoto et al reported that, especially in underweight patients with advanced COPD, inspiratory pressure load training might lead to tachypnea and wasted ventilation, which would in turn decrease exercise performance; however, this point was made as part of a case report [ 75 ]. Further studies are needed to evaluate the effect of expiratory or inspiratory pressure load training on exertional dyspnea in patients with COPD.…”
Section: Exercise Tolerance and Exercise-limiting Factorsmentioning
confidence: 99%